2017
DOI: 10.1007/s11899-017-0376-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Predictors of Treatment-Related Toxicity Among Children With Acute Lymphoblastic Leukemia

Abstract: Multiple studies have examined the toxicities of the primary chemotherapeutic agents used to treat childhood ALL in relation to host genetic factors. However, few results have been replicated independently, largely due to cohort differences in ancestry, chemotherapy treatment protocols, and definitions of toxicities. To date, there is only one widely accepted clinical guideline for dose modification based on gene status: thiopurine dosing based on TPMT genotype. Based on recent data, it is likely that this gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 99 publications
3
14
0
1
Order By: Relevance
“…However, in kidney transplant recipients receiving azathioprine, there was no association between this polymorphism and azathioprine dose requirements . Although the mechanisms of these SNPs have not been fully explained by previously published studies, these genetic polymorphisms in candidate genes with potential effects on the pharmacokinetics of thiopurine metabolism should be considered and validated with further studies …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in kidney transplant recipients receiving azathioprine, there was no association between this polymorphism and azathioprine dose requirements . Although the mechanisms of these SNPs have not been fully explained by previously published studies, these genetic polymorphisms in candidate genes with potential effects on the pharmacokinetics of thiopurine metabolism should be considered and validated with further studies …”
Section: Discussionmentioning
confidence: 96%
“…Despite a lower frequency of TPMT variant alleles in Asians, the incidence of thiopurine‐induced leukopenia is higher in Asians than in individuals of European descent . Studies have found an association between several genetic polymorphisms and toxicity in paediatric ALL patients, but the association varies among ethnic groups . For example, thiopurine‐related toxicity is frequently observed in Asian populations, with importance of the Nudix hydrolase 15 ( NUDT15 ) genotype rather than the thiopurine methyltransferase ( TPMT ) genotype …”
Section: Introductionmentioning
confidence: 99%
“…Several chemotherapeutic agents used in ALL treatment are also associated with neurotoxicities and seizures (9)(10)(11)(12)(13)(14)(15)(16) . Treatment of seizures is symptomatic but awareness of possible etiologies, such as PRES, infections or SVT, is important for timely diagnosis and optimal treatment (8,17,18) .…”
Section: Introductionmentioning
confidence: 99%
“…6-Mercaptopurine (6-MP) is concomitantly given with Methotrexate (MTX) during consolidation and maintenance. It is a purine antimetabolite, and it is frequently associated with life threatening myelosupression, though with major individual variability (Al-Mahayri et al, 2017; Maxwell and Cole, 2017; Rudin et al, 2017; Koutsilieri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Driven by this inter-individual variability, a number of investigators have extensively evaluated germline pharmacogenetic (PGx) markers with a focus on candidate pharmacokinetic and pharmacodynamic targets to predict 6-MP toxicity (Al-Mahayri et al, 2017; Maxwell and Cole, 2017; Rudin et al, 2017; Koutsilieri et al, 2019). The oldest and most robust evidence is currently for genetic variants in thiopurine-S-methyltransferase (TPMT), an enzyme that inactivates the drug.…”
Section: Introductionmentioning
confidence: 99%